Diet quality and ultra-processed food consumption among adolescent girls Aged 12-19 years old - Oktaviani, Endang; Ameline, Amanda Safiera; Htet, Min Kyaw; Fahmida, Umi (Indonesian Nutrition Association, 2025)
Healthy dietary patterns during adolescence are essential for achieving optimal nutrition, reducing the risk of obesity, and preventing non-communicable diseases (NCDs) in adulthood. However, the abundant availability and frequent consumption of ultra-processed foods (UPFs) and foods that are high in sugars, saturated fats, salt, and poor in essential nutrients contribute to poor diet quality, which may increase the risk of obesity and NCDs. Assessing adolescent diet quality is essential to support evidence-based public health interventions.